The International Tribunal for the Law of the Sea and the possibility to hear Algerian maritime disputes - eyazid, Ali; Nouar, Chahrazad (Journal of Human Sciences, 2021)
The International Tribunal for the Law of the Sea is considered one of the specialized international judicial bodies, which settles in one type of disputes, which are those related to the application and interpretation of the United Nations Convention on the Law of the Sea of ​​1982 and the conflicts that may arise from it. In front of her, with a study of practical examples of disputes in which the court had previously separated, and after Algeria’s determination of its maritime field in 2018, especially the exclusive economic zone, it appeared on the surface signs of a maritime dispute between Algeria and Spain and Italy regarding the borders of this region. This study examines the causes and future of this conflict and the extent to which the International Tribunal for the Law of the Sea can be considered and adjudicated in such a conflict.